2017
DOI: 10.1002/eco.1919
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative response of leaf‐litter decomposition rate to water abstraction in a gradient: Implications for environmental flow management

Abstract: Water abstraction significantly impacts streams and rivers, in turn affecting ecosystem structure and function. Previous studies have mostly focused on the response of structural indicators (e.g., invertebrate community composition) to water abstraction but have often neglected the indicators of ecosystem processes (e.g., decomposition rates). In this study, we investigated the relationship of leaf‐litter decomposition rate (k) with flow reduction in a manipulated ecosystem experiment. The flow reduction rate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…1). Many previous studies reported that the frequent alternation of inundation and stranding, the increase of stream flow, and the shoal water flooding all increased the decomposition rates, especially at the early stage of decomposition (Dolinar et al 2016, Zheng et al 2018b, Huang et al 2018). Moreover, Zheng et al (2018b) found that the duration of early‐stage inundation had a greater influence on the litter decomposition rate than the later stage inundation.…”
Section: Discussionmentioning
confidence: 99%
“…1). Many previous studies reported that the frequent alternation of inundation and stranding, the increase of stream flow, and the shoal water flooding all increased the decomposition rates, especially at the early stage of decomposition (Dolinar et al 2016, Zheng et al 2018b, Huang et al 2018). Moreover, Zheng et al (2018b) found that the duration of early‐stage inundation had a greater influence on the litter decomposition rate than the later stage inundation.…”
Section: Discussionmentioning
confidence: 99%